Rational Design and Synthesis of New, High Efficiency, Multipotent Schiff Base-1,2,4-triazole Antioxidants Bearing Butylated Hydroxytoluene Moieties - Yehye, Wageeh Abdulhadi; Abd Rahman, Noorsaadah; Saad, O.; Ariffin, Azhar; Hamid, Sharifah Bee Abd; Alhadi, A.A.; Kadir, F.A.; Yaeghoobi, M.; Matlob, A.A. (MDPI, 2016)
A new series of multipotent antioxidants (MPAOs), namely Schiff base-1,2,4-triazoles attached to the oxygen-derived free radical scavenging moiety butylated hydroxytoluene (BHT) were designed and subsequently synthesized. The structure-activity relationship (SAR) of the designed antioxidants was established alongside the prediction of activity spectra for substances (PASS). The antioxidant activities of the synthesized compounds 4-10 were tested by the DPPH bioassay. The synthesized compounds 4-10 inhibited stable DPPH free radicals at a level that is 10-4 M more than the well-known standard antioxidant BHT. Compounds 8-10 with para-substituents were less active than compounds 4 and 5 with trimethoxy substituents compared to those with a second BHT moiety (compounds 6 and 7). With an IC50 of 46.13 ± 0.31 μM, compound 6 exhibited the most promising in vitro inhibition at 89%. Therefore, novel MPAOs containing active triazole rings, thioethers, Schiff bases, and BHT moieties are suggested as potential antioxidants for inhibiting oxidative stress processes and scavenging free radicals, hence, this combination of functions is anticipated to play a vital role in repairing cellular damage, preventing various human diseases and in medical therapeutic applications.